2012
DOI: 10.1007/s11248-012-9645-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of AtbHLH17 and AtWRKY28 confers resistance to abiotic stress in Arabidopsis

Abstract: Stress adaptation in plants involves altered expression of many genes through complex signaling pathways. To achieve the optimum expression of downstream functional genes, we expressed AtbHLH17 (AtAIB) and AtWRKY28 TFs which are known to be upregulated under drought and oxidative stress, respectively in Arabidopsis. Multigene expression cassette with these two TFs and reporter gene GUS was developed using modified gateway cloning strategy. The GUS assay and expression analysis of transgenes in transgenic plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
98
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(99 citation statements)
references
References 53 publications
1
98
0
Order By: Relevance
“…Up-regulation of multiple TFs by water stress may lead to enhanced expression of target genes. Babitha et al (2013) showed that co-expression of AtWRKY28 and AtbHLH17 resulted in increased expression of different target genes in response to various abiotic stresses like drought, salt and oxidative stress in Arabidopsis (Babitha et al 2013). various downstream target genes like RD29A, rd22 and FSD2 were found to have w boxes in their promoter regions whereas KIN1 and ADH1 have G-box elements while P5C5 and LEA14 have both elements.…”
Section: Abiotic Stress and Wrky Transcription Factors: Altered Exprementioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of multiple TFs by water stress may lead to enhanced expression of target genes. Babitha et al (2013) showed that co-expression of AtWRKY28 and AtbHLH17 resulted in increased expression of different target genes in response to various abiotic stresses like drought, salt and oxidative stress in Arabidopsis (Babitha et al 2013). various downstream target genes like RD29A, rd22 and FSD2 were found to have w boxes in their promoter regions whereas KIN1 and ADH1 have G-box elements while P5C5 and LEA14 have both elements.…”
Section: Abiotic Stress and Wrky Transcription Factors: Altered Exprementioning
confidence: 99%
“…However, there is not a simple relationship between the presence or absence of binding sites and expression levels, genes having binding site for both classes of transcription factors do not show higher expression when compared with the ones which have just one of the two binding sites alone. However, it is clear that co-expression of multiple transcription factors leads to up-regulation of more targets (Babitha et al 2013). Hence, cooperative behavior of the different transcription factors appears to result in tighter regulation of the molecular responses to different stress conditions.…”
Section: Abiotic Stress and Wrky Transcription Factors: Altered Exprementioning
confidence: 99%
“…2,7,11,[65][66][67] It has also been reported recently that ectopic expression of stress specific transcription factors in combination aids in combating multiple abiotic stresses. [68][69][70] Large numbers of review articles have compiled the relevance of multiple upstream regulatory as well as downstream functional genes underlying a wide array of drought tolerance traits in imparting abiotic stress tolerance ( Table 2). There is a well defined and tightly regulated signaling network starting from stress signal perception up to downstream functional gene activation, and the genes which regulate their activity, whichever be the tolerance mechanism.…”
Section: Target Genes To Manipulate Cellular Tolerancestress Responsimentioning
confidence: 99%
“…Recently, Babitha et al (2012) have shown that co-expression of AtbHLH17 and AtWRKY28 confers resistance to abiotic stress in Arabidopsis. 23 The transgenic lines show enhanced tolerance to multiple abiotic stresses like drought, salt and oxidative stress via regulation of more number of targets.…”
mentioning
confidence: 99%
“…Recently, Babitha et al (2012) have shown that co-expression of AtbHLH17 and AtWRKY28 confers resistance to abiotic stress in Arabidopsis. 23 The transgenic lines show enhanced tolerance to multiple abiotic stresses like drought, salt and oxidative stress via regulation of more number of targets. Thus, we hypothesize utilizing the current knowledge reported in this study for GmWRKY53, which is a salt and water-stress inducible gene has full potential for being used as suitable candidate that will provide novel insights toward functionality in response to abiotic stress.…”
mentioning
confidence: 99%